The Broadband Nonlinear Optical Response in Graphene/MoS2/Ag Thin Films at Near Infrared - Sun, Di; Fang, Yu; Yan, Xiaoyan; Shan, Wen; Sun, Wenjun; Meng, Qingyu (Frontiers in Materials, 2021)
The graphene/MoS2/Ag thin films are successfully prepared by the magnetron sputtering techniques and liquid phase exfoliation. Structure, morphology, optical properties and nonlinear optical characteristics of the graphene/MoS2/Ag thin films are studied by X-ray diffractometer (XRD), spectrophotometer (Uv-Vis), field-scanning electron microscope (FE-SEM) and femtosecond (fs) Z-scan technique. The results of the fs Z-scan experiment indicate that the graphene/MoS2/Ag thin films exhibit the reverse saturable absorption (RSA) properties due to the free carrier absorption (FCA) and two-photon absorption (TPA). More importantly, with the increase of DC magnetron sputtering power (5 W to 15 W), the local surface plasmon resonance (LSPR) effect increases, which leads to the enhancement of nonlinear optical properties of the graphene/MoS2/Ag thin films. The nonlinear absorption coefficients of the graphene/MoS2/Ag thin films are increased from 1.14×10-14 cm/MW to 1.8×10-14 cm/MW at 800 nm, from 4.79×10-15 cm/MW to 6.79×10-15 cm/MW at 1030 nm. The nonlinear refraction index of the graphene/MoS2/Ag thin films are -4.37×10-19~-4.18×10-18 cm2/MW under the excitation of 800 nm and 1030 nm, respectively. Moreover, the nonlinear figure of merit (FOM) values of the graphene/MoS2/Ag thin films are increased from 1.23 to 2.91 and from 1.30 to 1.47 when the graphene/MoS2/Ag thin films are excited at 800 nm and 1030 nm respectively, which are enough to support the application of the graphene/MoS2/Ag thin films in the field of all-optical switching applications.